2021
DOI: 10.1007/s41614-021-00050-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature atmospheric discharge plasma and its applications for the surface treatment

Abstract: The atmospheric pressure low-temperature homogeneous discharge using helium and nitrogen, both known for industrial applications, was reviewed. In case of helium, metastable atoms (21s and 23s) produced in the glow discharge were able to dissociate mixed molecular gases to produce radicals or atoms. Radical species undergo chemical reactions, such as oxidation or nitration reaction and form products on the electrode surfaces. Applications of helium atmospheric pressure glow discharge including surface treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The authors suggested that for the controlled removal of a thin defective layer from the surface of ceramic products, physical processes (without intense temperature heating and mechanical action) can be used, which are based on the energy impact of directed flows of electrons, ions or neutral particles generated by various energy sources. A source of beams of accelerated ions and fast atoms of inert gases (argon) generated by low-temperature plasma of a glow discharge was chosen as a source of energy impact [58][59][60][61].…”
mentioning
confidence: 99%
“…The authors suggested that for the controlled removal of a thin defective layer from the surface of ceramic products, physical processes (without intense temperature heating and mechanical action) can be used, which are based on the energy impact of directed flows of electrons, ions or neutral particles generated by various energy sources. A source of beams of accelerated ions and fast atoms of inert gases (argon) generated by low-temperature plasma of a glow discharge was chosen as a source of energy impact [58][59][60][61].…”
mentioning
confidence: 99%